BIOETHICS AND SOCIAL RESPONSIBILITY CORPORATE TRAINING UPON FOR INTEGRAL UNIVERSITY - Gutiérrez Huby, Ana María (2013)
The main objective of the present article is to examine in depth the investigations generated concerning the bioethics, a scientific discipline that deals with the ethical problems concerning life and environment. We will examine its significance, domain, its relation with the social responsibility in the business management and the importance of its application in the education of the future generations of professionals. As main conclusion, is outlined the crucial need to incorporate this discipline into the university´s curricula as a basic element in the integral education. In this way we will provide an education in values that inculcates a culture of respect for life into all of the aspects of action of its students and thereby in all of their relations with the environment.